Sexual patterning and condom use among a group of HIV vulnerable men in Thika, Kenya. Issue 6 (30th November 2004) - Ferguson, A; Pere, M; Morris, C; Ngugi, E; Moses, S
Abstract : Background/aim: A composite sample of 37 peer educators and 215 members of self help groups of male informal sector workers in Thika, Kenya, targeting HIV/AIDS prevention, were interviewed about their sexual behaviour, using a customised template, as part of a broader survey on gender attitudes and peer pressure. Method: Details on each sexual partner reported by each man over a 12 month recall period included type of partner, months during which sexual relations took place, and condom use. Results: The men reported 471 sexual partners over the recall period, with a range of 0–16 partners, and an average of just under two partners. 8% of men had had no sexual partner, half were monogamous, and 3% had multiple partners with whom they used condoms exclusively, leaving 39% at varying degrees of risk. Condom use increased significantly with reduced intimacy of partner. 16% of men reported having at least one liaison with a female sex worker and two thirds of such liaisons were exclusively protected by condom use. Younger, single men had significantly more partners, but were more likely to use condoms. Duration of membership in self help groups was strongly associated with exclusive use of condoms with casual or FSW partners. Recorded attitudes corresponded somewhat with practice, but the data showed large gaps between the two, and low levels of gender sensitivity. Conclusion: There is some evidence that group membership has resulted in increased condom use and partner reduction, but there are doubts as to the extent to which the "ABC" strategy can be successful in stemming the HIV/AIDS epidemic. It may be necessary for interventions to target contextual issues, particularly gender relations, if the approach is to be more successful.